1997
DOI: 10.1128/jb.179.6.1880-1886.1997
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular melibiose and fructose are intermediates in raffinose catabolism during fermentation to ethanol by engineered enteric bacteria

Abstract: Contrary to general concepts of bacterial saccharide metabolism, melibiose (25 to 32 g/liter) and fructose (5 to 14 g/liter) accumulated as extracellular intermediates during the catabolism of raffinose (O-␣-D-galactopyranosyl-1,6-␣-D-glucopyranosyl-␤-D-fructofuranoside) (90 g/liter) by ethanologenic recombinants of Escherichia coli B, Klebsiella oxytoca M5A1, and Erwinia chrysanthemi EC16. Both hydrolysis products (melibiose and fructose) were subsequently transported and further metabolized by all three orga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

1998
1998
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 26 publications
1
15
0
Order By: Relevance
“…Complex nutrients are absent in MM and the rise in pH observed in this medium may be explained by cell lysis and release organic macromolecules that can be utilized by growing cells. The results obtained in this work for KO11 are similar to those observed in a previous study (24), in which greater than 90% of the maximum theoretical yield was reached upon fermentation of 9% sucrose. However, P2 presented poorer results than in that study, producing 73% of the maximum theoretical yield with 8% sucrose and 58% with 12% sucrose.…”
Section: Discussionsupporting
confidence: 91%
“…Complex nutrients are absent in MM and the rise in pH observed in this medium may be explained by cell lysis and release organic macromolecules that can be utilized by growing cells. The results obtained in this work for KO11 are similar to those observed in a previous study (24), in which greater than 90% of the maximum theoretical yield was reached upon fermentation of 9% sucrose. However, P2 presented poorer results than in that study, producing 73% of the maximum theoretical yield with 8% sucrose and 58% with 12% sucrose.…”
Section: Discussionsupporting
confidence: 91%
“…They found that the hydrolysis efficiencies of raffinose and melibiose after 120 h were below 25% and 50% in the media that contained 50 g dm −3 and 20 g dm −3 of these sugars, respectively. In another study, Moniruzzaman et al 12 found that the hydrolysis efficiencies of raffinose after 24 h with E chrysanthemi, K oxytoca and E coli were 73%, 69% and 43%, respectively, in the media that contained this sugar in a concentration of 90 g dm −3 . However, raffinose and produced melibiose were completely hydrolyzed by E chrysanthemi and K oxytoca after 144 h from the beginning of the process, and more than 83% of the produced galactose accumulated in the fermentation media.…”
Section: Discussionmentioning
confidence: 97%
“…These facts were taken into consideration for a development of recombinant strains of baker's yeasts that produce α-galactosidase. 7 -10 Recombinant bacteria strains that ferment raffinose, such as Zymomonas mobilis, 11 Escherichia coli, Klebsiella oxytoca and Erwinia chrysanthemi 12 were developed for ethanol production. However, raffinose was not completely utilized and low ethanol yields were obtained with these microorganisms.…”
Section: Introductionmentioning
confidence: 99%
“…Cornelis et al (1978) reported that raffinose can be transported by the lactose permease, and isolated lacI constitutive mutants of E. coli K-12 capable of raffinose uptake and metabolism. Moniruzzaman et al (1997) isolated raffinose positive mutants of KO11, a derivative of E. coli B, by culture enrichment in presence of raffinose and the adapted strain may contain an analogous mutation.…”
Section: Fermentation Of Galactose Sucrose Raffinose and Stachyosementioning
confidence: 99%